FULL E-BOOK INDONESIAN LAW JOURNAL VOLUME 17 N0. 1, 2024 - Nofli; Puspita, Rona; Sari, Fitri Amalia; Irianto, Khairunnisa; Tisna, Ayu Bulan; Rezara, Juvelin; Rahman, Rafika Rizky Aulia; Iswara, Rizka (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
The 2024's first edition of Indonesian Law Journal Volume 16 has been published. The discussion topic of this edition is The Role of the International Court of Justice (ICJ) and Its Legally Binding Advisory Opinions in Dealing with Armed Conflicts and State Responsibility in Handling Foreign Refugees. This edition presents 6 (six) articles from authors with various backgrounds. Please enjoy reading as we hope these article in our Journal are beneficial and constructive towards the development of national law.